2018
DOI: 10.3389/fmicb.2018.02935
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Quantification and STAT3 Expression in a Human Skin Organ Culture Model for Innate Immunity to Herpes Zoster

Abstract: The goal of this project was to document the autophagy response in human neonatal skin organ culture (SOC) after infection with varicella-zoster virus (VZV). The VZV-infected SOC model has attributes of herpes zoster, in that an injection of virus into the skin is analogous to exit of virus from the sensory nerve termini into skin during herpes zoster. Cultures were maintained for 28 days and periodically examined for an autophagy response by quantitation of autophagosomes with Imaris software. Expression of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…We have reproduced these results both in infected cell cultures and in infected human skin xenografts within the severe combined immunodeficient (SCID) mouse model for varicella (8, 9). More recently, these results have been duplicated in a human skin organ culture model for herpes zoster infection (10). In another set of experiments, we documented autophagic flux in VZV-infected cells (9).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…We have reproduced these results both in infected cell cultures and in infected human skin xenografts within the severe combined immunodeficient (SCID) mouse model for varicella (8, 9). More recently, these results have been duplicated in a human skin organ culture model for herpes zoster infection (10). In another set of experiments, we documented autophagic flux in VZV-infected cells (9).…”
Section: Introductionmentioning
confidence: 91%
“…Cells exhibit basal levels of autophagy even during herpesvirus infection (13). However, the levels of autophagy induced by VZV infection in both (i) human skin during the VZV disease called herpes zoster (shingles) and (ii) human skin explants in either the skin organ culture model or the severe combined immunodeficient mouse model of VZV infection are far above basal levels (10). Further, we found that inhibition of autophagy diminishes VZV cell-to-cell spread and infectivity (8).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, HeLa cells transfected with VZV glycoproteins presented with an enlarged ER and increased LC3-punctae formation [45]. Importantly, these results, obtained in cell cultures, have been confirmed and extended to human skin biopsies, human skin organ cultures and the severe combined immunodeficiency mouse model transplanted with human skin [45,48,51]. Observations in human skin further add to the biological relevance of the findings, illustrating autophagy to be a factor involved in disease pathogenesis, as confirmed by studies in human skin organ cultures, in which a significant increase in autophagic vesicles upon VZV infection was demonstrated [51].…”
Section: Activation Of Autophagy Flux During Vzv Infectionmentioning
confidence: 61%
“…Us3-like kinases may allow viruses lacking ICP34.5 to limit autophagy. Not all α-herpesviruses,however, limit autophagy, as autophagy is induced in cells infected with varicella-zoster virus (55,56). The overall extent to which the substrate specificity of other α-herpesvirus Us3 homologs overlaps with HSV-1 Us3, however, remains to be defined and could be a defining determinant that limits autophagy.…”
Section: Discussionmentioning
confidence: 99%